Diammonium hydrogenphosphate for the consolidation of building materials. Investigation of newly-formed calcium phosphates. (20th January 2019) - Possenti, Elena; Colombo, Chiara; Conti, Claudia; Gigli, Lara; Merlini, Marco; Plaisier, Jasper Rikkert; Realini, Marco; Sali, Diego; Gatta, G. Diego
Graphical abstract: Highlights: Diammonium hydrogenphosphate (DAP) solutions consolidate decayed carbonatic stones. The formed phases depend on treatment method, DAP molarity and stone microstructure. Cutting-edge techniques are discussed to identify similar crystalline phases. The formation of hydroxyapatite is unambiguously demonstrated. Variables which might affect the treatment effectiveness are discussed. Abstract: Diammonium hydrogenphosphate (DAP) is a water soluble consolidant for decayed carbonatic materials of historical buildings. The reaction of DAP solutions with polycrystalline calcite of marbles is non-stoichiometric and forms a calcium phosphates mixture whose identification is tricky and controversial. This study investigated how the DAP molarity, the treatment method and the microstructure of the stone influence the formation of specific phases. Thermal treatments and cutting-edge techniques (XRD with synchrotron radiation in transmitting geometry and high resolution FTIR microspectroscopy) were used to overcome the analytical limits of the more conventional methods, shading light to an in depth evaluation of DAP consolidating processes and treatment conditions.